Same and Different: Epistemic Topicalizations as Resources for Cohesion and Change in Classroom Learning Trajectories. Issue 8 (17th November 2018) - Tanner, Marie; Sahlström, Fritjof
ABSTRACT: Despite a seemingly fragmented interactional context, teachers and students in classrooms routinely manage to co-construct coherent, inter-related, and individually adapted learning trajectories distributed over days and weeks. The aim of this article is to explore with what interactional resources progressivity is accomplished in learning trajectories by focusing on how participants establish relations of cohesion and change between current and previous occasions that constitute a learning trajectory. Analysis of empirical data shows how participants frequently topicalize aspects of epistemic stance toward a co-constructed learning content. Such epistemic topicalizations play an important role in maintaining cohesion in a learning trajectory, while making it possible for teachers and students to progressively change and differentiate their epistemic stance. Epistemic topicalizations are suggested as a useful analytic concept, grounded in conversation analysis, to describe how cohesion and change are emically managed in interaction to accomplish progressivity in learning trajectories.